Analisis Efektivitas Organisasi Dalam Program Pelayanan Administrasi Terpadu Kecamatan (PATEN) Di Kecamatan Gunungpati Kota Semarang - Tias Vela Erdina; Dyah Hariani (Journal of Public Policy and Management Review, 2017)
Public services with good quality is required by community. The government passed a regulation that Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 Tentang Pedoman Pelayanan Administrasi Terpadu Kecamatan (PATEN) to create public service with good quality. PATEN aims to improve the quality of service and bring the service closer to the community. The purpose of this study are to describe and try to analize organizational effectiveness of subdistrict integrated administrative services program in Subdistrict Gunungpati Semarang and to describe any proponent or resistor factors which influence effectiveness of District Gunungpati’s Office. The results of this study is shown that organizational effectiveness of PATEN in Subdistrict Gunungpati Semarang is as expected. In the source approach, it can be seen that PATEN support facilities are available enough to be utilized by the community. Then on the process approach, communication is created dynamically and always apply the discussion. But still have constraints on the environmental characteristics of the limited number of employees and the extent of Gunungpati District as well as differences in educational background of local communities. The researcher suggested optimizing the role of kelurahan to implement the “ball picking” system and the orientation of the employees in providing the service should always be oriented to the private sector so that the attitude of the employees can be more flexible to adjust the background of the people who come.